2021
DOI: 10.1016/j.redox.2021.101904
|View full text |Cite
|
Sign up to set email alerts
|

bFGF alleviates diabetes-associated endothelial impairment by downregulating inflammation via S-nitrosylation pathway

Abstract: Protein S-nitrosylation is a reversible protein modification implicated in both physiological and pathophysiological regulation of protein function. However, the relationship between dysregulated S-nitrosylation homeostasis and diabetic vascular complications remains incompletely understood. Here, we demonstrate that basic fibroblast growth factor (bFGF) is a key regulatory link between S-nitrosylation homeostasis and inflammation, and alleviated endothelial dysfunction and angiogenic defects in diabetes. Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Besides, the alive UCMSC cells in the bFGF-ECM-HP hydrogel were more than that in the ECM-HP hydrogel after being cultured for 48 h. The outcomes of CCK-8 assay revealed that bFGF promoted the expansion of UCMSC and improved the survival rate of UCMSC in vitro (Figure B). Numerous studies have shown that bFGF could enhance neuronal cell fate determination and differentiation. , UCMSC has the capability to naturally release multicytokines and differentiate into nerve cells. , To gain further insights into the interactions between bFGF and UCMSC, the content of bFGF was measured by ELISA. In Figure C, the results of ELISA showed that UCMSC secreted a large number of bFGF significantly by bFGF stimulation during culture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the alive UCMSC cells in the bFGF-ECM-HP hydrogel were more than that in the ECM-HP hydrogel after being cultured for 48 h. The outcomes of CCK-8 assay revealed that bFGF promoted the expansion of UCMSC and improved the survival rate of UCMSC in vitro (Figure B). Numerous studies have shown that bFGF could enhance neuronal cell fate determination and differentiation. , UCMSC has the capability to naturally release multicytokines and differentiate into nerve cells. , To gain further insights into the interactions between bFGF and UCMSC, the content of bFGF was measured by ELISA. In Figure C, the results of ELISA showed that UCMSC secreted a large number of bFGF significantly by bFGF stimulation during culture.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that bFGF could enhance neuronal cell fate determination and differentiation. 24,25 UCMSC has the capability to naturally release multicytokines and differentiate into nerve cells. 26,27 To gain further insights into the interactions between bFGF and UCMSC, the content of bFGF was measured by ELISA.…”
Section: Bfgf Enhanced the Proliferation And Neural Differentiation O...mentioning
confidence: 99%
“…60 Due to its protective effect on endothelial impairment and chronic inflammation induced by hyperglycemia via the S-nitrosylation pathway, the bFGF has provided new insights into the management of nonhealing diabetic ulcers and associated lesions. 61 Considering the short half-life of bFGF and enzymatic degradation, various delivery systems have been tested for controlling the release of such growth factors. 20,21 In Figure 8.…”
Section: ■ Discussionmentioning
confidence: 99%
“…23 479) using the manufacturer's instructions. [ 97 ] A fresh brain was used for this assay. The homogenate was prepared in PBS and filtered with a 10WCO centrifuge tube.…”
Section: Methodsmentioning
confidence: 99%